2020
DOI: 10.3390/bs10070116
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Exercise and Behavioral Therapy for Depression and Anxiety: Systematic Review and Meta-Analysis

Abstract: Behavioral therapy (BT) and exercise are efficacious treatments for depression and anxiety when employed separately. The combination of BT and exercise (BT+Ex) may augment improvements but the combined effect of these therapies is not fully elucidated. The purpose of this meta-analysis was to determine if BT+Ex yielded a significant reduction in depression and anxiety symptoms compared to BT alone (BT). Randomized controlled studies published prior to September 2019 were searched among several databases (PUBME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
2
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 52 publications
1
13
2
2
Order By: Relevance
“…As the BPT concept focuses on established factors of action taken from CBT therapies, such as exposure training, problem solving, and the practising of new functional behaviour, BPT should not be seen as a different therapy but as an enrichment and implementation of CBT methods on the bouldering wall. Our results show that it is at least not inferior to CBT alone, a finding that is in line with current meta‐analyses that have shown that the combination of physical activity and psychotherapeutic methods (i.e., behavioural therapies) might go beyond the effect of psychotherapy alone (Bourbeau et al., 2020) and that physical activity is effective in reducing depression (Cooney et al., 2013) to a comparable extent as antidepressants (Blumenthal et al., 2007) or psychotherapy alone. Both therapies in this study are group therapies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As the BPT concept focuses on established factors of action taken from CBT therapies, such as exposure training, problem solving, and the practising of new functional behaviour, BPT should not be seen as a different therapy but as an enrichment and implementation of CBT methods on the bouldering wall. Our results show that it is at least not inferior to CBT alone, a finding that is in line with current meta‐analyses that have shown that the combination of physical activity and psychotherapeutic methods (i.e., behavioural therapies) might go beyond the effect of psychotherapy alone (Bourbeau et al., 2020) and that physical activity is effective in reducing depression (Cooney et al., 2013) to a comparable extent as antidepressants (Blumenthal et al., 2007) or psychotherapy alone. Both therapies in this study are group therapies.…”
Section: Discussionsupporting
confidence: 92%
“…It has been known for a long time that body‐related interventions can have strong effects on mental states (Barnard & Teasdale, 1991). In recent studies, physical activity has been shown to be effective in the treatment of depression in general (Gordon et al., 2018; Schuch et al., 2016) and particularly when it is used to augment the effects of psychotherapy (Bourbeau, Moriarty, Ayanniyi, & Zuhl, 2020; NICE, 2009). Physical activity is even explicitly recommended in the current guidelines as a method that can complement the treatment of depression (DGPPN, 2015; NICE, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, physical activity is important for managing symptoms of depression and anxiety 26 28 . The therapeutic benefits of exercise in managing mental health are most prominent when used in combination with standard treatment, although it can also be efficacious as a stand-alone therapy, albeit with smaller effect sizes 29 , 30 . During the COVID-19 lockdown period, Zhang et al 31 found that either too little or too much physical activity worsened negative emotions including depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, physical activity is important for managing symptoms of depression and anxiety [26][27][28] . The therapeutic bene ts of exercise in managing mental health are most prominent when used in combination with standard treatment, although it can also be e cacious as a stand-alone therapy, albeit with smaller effect sizes 29,30 . During the COVID-19 lockdown period, Zhang, Zhang, Ma, and Di 31 found that either too little or too much physical activity worsened negative emotions including depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%